Home infusion teaching practices at federally funded hemophilia treatment centers in the United States of America. Issue 1 (20th June 2017) - Santaella, Maria E.; Bloomberg, Maya; Anglade, Debbie
Abstract: Essentials Hemophilia nurses are expected to teach home infusion (HI) to patients and their caregivers. A survey was conducted to identify current HI teaching practices in the United States of America. Some nurses reported lacking confidence to teach; curricula exist but their use is not uniform. The study supports the development of national guidelines and a standard curricula to teach HI. Background: Home management of hemophilia is standard of care in many countries. This study examined current nursing practices in teaching home infusion (HI) at hemophilia treatment centers (HTC) in the USA. Objectives: The aims were to identify and compare tools and resources used, areas of unmet needs, and to discuss implications for nurses in practice. Methods: An anonymous electronic survey was distributed to 574 HTC nurses; 156 responses were analyzed. Results: The data demonstrated that nurses, more specifically nurse coordinators, were most responsible for teaching HI. However, many nurses lack the knowledge and confidence to do so: 23.0% responded feeling somewhat or not very confident with teaching. Of those 36.4% were staff nurses, 11.9% nurse coordinators, and 41.7% advanced practice registered nurses. The majority of nurses have worked more than 5 years as a nurse, with a mean length of time of 23.7 years (SD=11.12, range 3‐47) and a mean of 12.9 years (SD=10.29, range 1‐42) in a HTC. Thirty‐eight and a half percent of nurses have worked less than 5 years in a HTC. Most nurses appeared to follow the Infusion Nurses Society standards when performing venipunctures. Many centers reported using a formal tool or curriculum to teach HI. Nonetheless, these curricula are not uniform and their use is inconsistent between centers and regions. Conclusion: There are currently no national guidelines or standards to assist nurses in this task. The data confirmed the need to develop guidelines and a standardized curriculum to teach HI.